2014
DOI: 10.1002/syn.21756
|View full text |Cite
|
Sign up to set email alerts
|

The potential ofo-bromo-trans-decalinvesamicol as a new PET ligand for vesicular acetylcholine transporter imaging

Abstract: We investigated the characteristics of the regional rat brain distribution of radio-brominated o-bromo-decalinvesamicol (OBDV) in vivo to evaluate its potential as a PET ligand for vesicular acetylcholine transporter (VAChT). In in vivo biodistribution study, the specific brain regional accumulation of [(77) Br]OBDV was revealed 30 min after intravenous injection. The specific brain regional accumulation of [(77) Br]OBDV was significantly inhibited by co-injection of (+/-)-vesamicol. In contrast, no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The influence of enantioselectivity of the vesamicol analogs FEOBV ( 2 ) [ 45 ], MIBT ( 8 ) [ 55 ], FBT ( 9 ) [ 60 ], oIV ( 10 ) [ 62 ], OMV ( 11 ) [ 63 ], OIDV ( 13 ) [ 67 ], FBBV ( 18 ) [ 78 ], 19 [ 81 ], TZ659 ( 20 ) [ 82 ], VAT ( 21 ) [ 83 ], and 22 [ 84 ] on the binding affinity for VAChT, σ 1 , and σ 2 receptors was reported. The investigated vesmicol analogs except for MIBT ( 8 ) and FBT ( 9 ) showed that (−)-enantiomers had about 3- to 29-fold higher binding affinity for VAChT than (+)-enantiomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of enantioselectivity of the vesamicol analogs FEOBV ( 2 ) [ 45 ], MIBT ( 8 ) [ 55 ], FBT ( 9 ) [ 60 ], oIV ( 10 ) [ 62 ], OMV ( 11 ) [ 63 ], OIDV ( 13 ) [ 67 ], FBBV ( 18 ) [ 78 ], 19 [ 81 ], TZ659 ( 20 ) [ 82 ], VAT ( 21 ) [ 83 ], and 22 [ 84 ] on the binding affinity for VAChT, σ 1 , and σ 2 receptors was reported. The investigated vesmicol analogs except for MIBT ( 8 ) and FBT ( 9 ) showed that (−)-enantiomers had about 3- to 29-fold higher binding affinity for VAChT than (+)-enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…OBDV is a vesamicol analog having a decalin skeleton (as A ring) and a 4-(2-bromophenyl)piperidine moiety [ 67 ]. The binding affinity (Ki) of OBDV ( 14 ) to VAChT, σ 1 , and σ 2 was 13.8 nM (rat brain), 150.7 nM (rat brain), and 137.5 nM (rat liver), respectively, and the binding affinity (Ki) of vesamicol to VAChT, σ 1 , and σ 2 was 33.9 nM (rat brain), 22.1 nM (rat brain), and 86.7 nM (rat liver), respectively.…”
Section: Vacht Imaging Agent Based On Vesamicol Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…imaging probe, PET, VAChT, vesamicol analog (Bar & Parsons 1986;Marshall & Parsons 1987), many vesamicol analogs have been developed as potential VAChT imaging agents for PET or SPECT (Azim et al, 2014;Bando et al, 2001;Barthel et al, 2015;Custers, Leysen, Stoof, & Herscheid, 1997;Efange, Michelson, Khare, & Thomas, 1993;Efange et al, 1994, Efange et al, 2000Kitamura et al, 2016;Kozaka et al, 2014;Mulholland et al, 1998;Shiba, Mori, & Tonami, 2003;Sorger et al, 2000Sorger et al, , 2008Sorger et al, , 2009. Furthermore, several reported vesamicol analogs were separated into optical isomers to improve in vitro and in vivo characteristics as VAChT imaging agents (Efange et al, 1994;Jung, Van Dort, Gildersleeve, & Wieland, 1990;Kovac et al, 2010;Li et al, 2013;Mulholland et al, 1998;Shiba et al, 2003Shiba et al, , 2009Tu et al, 2009Tu et al, , 2015Uno et al, 2016).…”
Section: Introductionmentioning
confidence: 99%